Dupilumab for cancer-associated refractory pruritus - Aviv Talmon, MD; Shlomo Elias, MD, PhD; Limor Rubin, MD; Yaarit Ribak, MD; Eyal Ben Dori, MD; Oded Shamriz, MD; Michal Lotem, MD; Irit Adini, PhD; Yuval Tal, MD, PhD (Journal of Allergy and Clinical Immunology: Global, 2023)
Background: Pruritus can be an intolerable symptom in patients with cancer. Type 2 inflammation, and specifically, the cytokines IL-4, IL-13, and IL-31, play major roles in the itching process. Dupilumab is an antibody against IL-4Rα, which is a common IL-4 and IL-13 receptor subunit. Blocking IL-4 and IL-13 activity reduces the synthesis of IL-31, the “itch cytokine,” and receptors for these 3 cytokines are expressed on itch nerves. Dupilumab is approved for treating moderate-to-severe atopic dermatitis, of which itching is a significant symptom. Objective: The objective of this case study was to present the initial evidence of the safety and efficacy of dupilumab as a treatment for intractable malignancy-associated pruritus in 3 patients, thereby providing a basis for further investigation in a larger cohort. Methods: As a proof of concept, we used dupilumab in our center to treat 3 patients with intractable malignancy-associated pruritus. The first patient was a 73-year-old male with a history of prostate cancer, the second patient was a 75-year-old female with cutaneous T-cell lymphoma, and the third patient was a 32-year-old male with metastatic melanoma. All 3 patients experienced debilitating itching, which started at some stage after the malignancy had been diagnosed. Moreover, none of the 3 patients showed clinical evidence of atopic dermatitis or other causes of itching (eg, uremia or liver failure), and none of the 3 patients responded to conventional treatments for pruritus. Results: Biweekly treatment with dupilumab led to an immediate improvement in itching, which subsided entirely after a few doses without any significant adverse effects. Conclusion: We propose that dupilumab is a safe and effective treatment for intractable malignancy-associated pruritus, and we are currently testing it in a large cohort.